Inclusive globalization: unpacking China's Belt and Road Initiative. Issue 3 (3rd November 2016) - Liu, Weidong; Dunford, Michael
ABSTRACT: China's Belt and Road Initiative (BRI) is a call for an open and inclusive (mutually beneficial) model of cooperative economic, political and cultural exchange (globalization) that draws on the deep-seated meanings of the ancient Silk Roads. While it reflects China's rise as a global power, and its industrial redeployment, increased outward investment and need to diversify energy sources and routes, the BRI involves the establishment of a framework for open cooperation and new multilateral financial instruments designed to lay the infrastructural and industrial foundations to secure and solidify China's relations with countries along the Silk Roads and to extend the march of modernization and poverty reduction to emerging countries.